The Window of Implantation Is Closed by Estrogen via Insulin-Like Growth Factor 1 Pathway - R Kobayashi; J Terakawa; T Omatsu; Y Hengjan; T Mizutani; Y Ohmori; E Hondo (JRI, 2017)
Background: The opening and closing of the implantation window is important for successful pregnancy in eutherians. The recent study demonstrated that the window of uterine receptivity was prepared by the sole action of progesterone in mice, but the mechanism to close the window remained to be elucidated. Methods: The pregnant mice were ovariectomized on the evening on the third day of pregnancy with a single injection of medroxyprogesterone acetate to induce delayed implantation (DI). Several treatments were applied to DI mice. The uterine receptivity after treatment was assessed by examining cell proliferation in the uterine luminal epithelium (LE). The gene expressions in the endometrium were investigated by RNA-seq. The p<0.05 was considered significant. Results: Cell proliferation in the LE ceased only when the window of implantation was open. Estrogen (E2) stimulated cell proliferation in the LE rendered the uterus refractory. The high throughput gene expression analysis by RNA-Seq showed that the insulin-like growth factor 1 (IGF1) pathway was the candidate to close the implantation window under E2. In vivo administration of IGF1 to delayed implantation mice resulted in proliferation in the LE cells. Conclusion: This study demonstrated that the window of uterine receptivity was closed by E2, which was mediated by the IGF1 pathway.